DEVELOPMENT OF NOVEL FLOW FIELDS FOR PEM FUEL CELLS: NUMERICAL SOLUTION AND EXPERIMENTAL VALIDATION - Gelis, Kadir; Sahin, Bayram; Yurtcan, Ayse Bayrakceken (BEGELL HOUSE INC, 2022)
In the present study, the main purpose is to design flow channels with less pressure drop and higher performance compared to single serpentine flow channels which are found in the literature for PEM fuel cells. Within the scope of the present study, a numerical and experimental research was conducted on the design of the flow channels on bipolar plates. The fuel cell with a serpentine flow field was experimentally tested under conditions of 70 degrees C temperature, 1 atm pressure, 100% humidification, and 0.25 L/min anode/cathode flow rate, and analyzed numerically. This way, a numerical model verified with experimental data was obtained. Four models (Models 1-4) with unique flow fields were designed and numerically analyzed to compare with the verified numerical model. The flow field percentages (channel to rib ratio) of the 5 models (1 serpentine-type model + 4 new models) designed were fixed at a value of approximately 55.4%. For all designs, the channel width was set to 1.5 mm and the channel depth was set to 1 mm. Results indicate that the experimental data obtained were in accordance with the numerical results with an error margin of 5.3%. Based on the numerical analysis results at 0.6 V, current density increased by 23.9% in Model 1, 26.9% in Model 2, and by 13.8% in Model 3 compared to the reference model while a 12% decrease was observed in Model 4.
Keywords: flow field design; PEM fuel cell; bipolar plate; pressure drop; numerical analysis; COMPUTATIONAL FLUID-DYNAMICS; PRESSURE-DROP; DIAGNOSTIC-TOOL; BIPOLAR PLATES; MEMBRANE; PERFORMANCE; CHANNEL; MODEL; OPTIMIZATION; SIMULATION; Thermodynamics